Effect of Different Antibiotic Chemotherapies on Pseudomonas aeruginosa Infection In Vitro of Primary Human Corneal Fibroblast Cells - del Mar Cendra, Maria; Christodoulides, Myron; Hossain, Parwez (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is a major cause of bacterial keratitis (BK) worldwide. Inappropriate or non-optimal antibiotic chemotherapy can lead to corneal perforation and rapid sight loss. In this study, we tested the hypothesis that P. aeruginosa strain PAO1 invades primary human corneal fibroblasts (hCFs) in vitro and persists intracellularly, despite chemotherapy with antibiotics used commonly to treat BK. In rank order, ciprofloxacin, levofloxacin and polymyxin B showed the highest activity against planktonic PAO1 growth (100% inhibitory concentration ≤10 µg/mL; 50% inhibitory concentration ≤1 µg/mL), followed by gentamicin and ofloxacin (100% inhibitory concentration ≤50 µg/mL; 50% inhibitory concentration ≤10 µg/mL). These bactericidal antibiotics (50-200 µg/mL concentrations) all killed PAO1 in the extracellular environment of infected hCF monolayers. By contrast, the bactericidal antibiotic cefuroxime and the bacteriostatic antibiotic chloramphenicol failed to sterilize both PAO1 broth cultures, even at a concentration of ≥200 µg/mL) and infected hCF monolayers. Statistically, all antibiotics were able to prevent LDH release from PAO1-infected hCF monolayers at both concentrations tested. Intracellular Pseudomonas were significantly reduced (>99%, P<0.05) following treatment with ciprofloxacin, levofloxacin and ofloxacin, whereas gentamicin, polymyxin B and cefuroxime failed to clear intracellular bacteria over 24 h. Intracellular Pseudomonas infection was resistant to chloramphenicol, with hCF death observed by 9 h. Eventual growth of remaining intracellular Pseudomonas was observed in hCF after removal of all antibiotics, resulting in re-infection cycles and cell death by 48 h. All of the antibiotics reduced significantly (P<0.05) IL-1β secretion by hCF infected with a Multiplicity Of Infection (MOI) =1 of PAO1. With higher MOI, no pro-inflammatory effects were observed with antibiotic treatment, expect with polymyxin B and ofloxacin, which induced significant increased IL-1β secretion (P<0.001). The findings from our study demonstrated that bactericidal and bacteriostatic antibiotics, routinely used to treat BK, failed to eradicate Pseudomonas infection of hCFs in vitro and that their bactericidal efficacies were influenced by the cellular location of the organism.